2020
DOI: 10.1177/1073858420954826
|View full text |Cite
|
Sign up to set email alerts
|

Meninges: A Widespread Niche of Neural Progenitors for the Brain

Abstract: Emerging evidence highlights the several roles that meninges play in relevant brain functions as they are a protective membrane for the brain, produce and release several trophic factors important for neural cell migration and survival, control cerebrospinal fluid dynamics, and embrace numerous immune interactions affecting neural parenchymal functions. Furthermore, different groups have identified subsets of neural progenitors residing in the meninges during development and in the adulthood in different mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 119 publications
0
26
0
Order By: Relevance
“…1H-K). NPs in meninges are characterized by features of radial glia-like cells expressing GLAST and of immature neurons expressing β3-Tubulin [13]. We found that both GLAST + neural precursors and β3-Tubulin + cells increased in the treated group compared to the control (Fig.…”
Section: Neural Precursor Cells and Immature Neurons Increase In Mouse Brain Meninges Following Fluoxetine Administrationmentioning
confidence: 56%
See 2 more Smart Citations
“…1H-K). NPs in meninges are characterized by features of radial glia-like cells expressing GLAST and of immature neurons expressing β3-Tubulin [13]. We found that both GLAST + neural precursors and β3-Tubulin + cells increased in the treated group compared to the control (Fig.…”
Section: Neural Precursor Cells and Immature Neurons Increase In Mouse Brain Meninges Following Fluoxetine Administrationmentioning
confidence: 56%
“…[11]. Recently, a subset of meningeal-residing neural progenitors has been identified both during development and adulthood in different mammals, including humans [11][12][13][14][15][16]. Single-cell RNA sequencing (scRNAseq) analysis of meningeal cells identified a small fraction of cells with a signature corresponding to radial glia-like cells, expressing GLAST and a population with a neuroblast signature expressing β3-Tubulin [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the arachnoid membrane in regulating CSF composition is understudied. Emerging evidence indicates the importance of the meninges as a niche for neural progenitor cells [60]. These cells may be a therapeutic target for treating neurological disorders.…”
Section: Meningesmentioning
confidence: 99%
“…Karakatsani et al highlighted the many interactions between blood vessels and stem cells in the brain. Similarly to adult stem cells from different tissues (e.g., pancreas, liver, and adipose tissue), neural stem cells reside in close proximity to specialized blood vessels, which are highly organized with unique architecture characterized by dense network of planar, interconnected, and relatively non-tortuous (straight) vessels (Bifari et al, 2017b;Knobloch and Jessberger, 2017;Decimo et al, 2020). Importantly, specialized blood vessels at the NSC niche have partially permeable blood brain barrier (BBB) allowing the access of signals deriving from the blood.…”
Section: Metabolic Regulation Of Stem Cells and Tissue Growthmentioning
confidence: 99%